2005
DOI: 10.1081/jdi-48236
|View full text |Cite
|
Sign up to set email alerts
|

Silent Myocardial Ischemia and High-Grade Ventricular Arrhythmias in Patients on Maintenance Hemodialysis

Abstract: The occurrence of silent myocardial ischemia (SMI) and serious arrhythmias during hemodialysis (HD) has been well documented. However, it is unclear whether these changes are due to epicardial coronary artery disease (CAD). We conducted a prospective study to assess whether SMI and arrhythmias during HD correlated with angiographically demonstrable CAD. Twenty-three patients with end-stage renal disease on maintenance HD underwent 48-hour Holter monitoring, beginning 24 hours prior to a HD session. All patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 19 publications
(8 reference statements)
0
19
0
Order By: Relevance
“…Repeated episodes of stunning are cumulative and contribute to the pathophysiology of heart failure (4). We and other investigators have previously shown evidence that subclinical ischemia occurs in response to the stress of hemodialysis (5)(6)(7). We also demonstrated that it was possible to reduce the frequency and the severity of this phenomenon by using biofeedback dialysis (Hemocontrol, Gambro-Hospal, Mirandora, Italy) to improve the hemodynamic tolerability of dialysis.…”
mentioning
confidence: 78%
See 1 more Smart Citation
“…Repeated episodes of stunning are cumulative and contribute to the pathophysiology of heart failure (4). We and other investigators have previously shown evidence that subclinical ischemia occurs in response to the stress of hemodialysis (5)(6)(7). We also demonstrated that it was possible to reduce the frequency and the severity of this phenomenon by using biofeedback dialysis (Hemocontrol, Gambro-Hospal, Mirandora, Italy) to improve the hemodynamic tolerability of dialysis.…”
mentioning
confidence: 78%
“…The echocardiographic findings of dialysisinduced LV RWMA that were seen in both our previous study and in these results are strongly suggestive of subclinical ischemia, analogous to dobutamine stress echocardiography (16). In addition to the work from our center, one study demonstrated dialysis-induced perfusion defects using single photon emission computed tomography (7), and there are 10 reports of silent intradialytic ST depression detected by Holter monitoring (6,(17)(18)(19)(20)(21)(22)(23)(24)(25). Although initially there was concern that some electrocardiographic changes that were observed during dialysis were related to changes in electrolyte concentrations as opposed to myocardial hypoperfusion, the demonstration of dialysis-induced ischemia by electrocardiographic, echocardiographic, and isotopic techniques certainly suggests that such findings are attributable to ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of Hamidreza Nasri et al mean age was 47.9 16.1 year 9 . In other studies the mean age of patients had been reported from 38.2 year in 1997 to 52.5 in 2007 10,18,19 . It seems better control and management of disease leading to dialysis leads to later presentation of renal complications.…”
Section: Discussionmentioning
confidence: 99%
“…In a study Holter monitoring showed silent MI in 22% cases during dialysis 19 . A significant increase happened in the frequency of ventricular arrhythmias during and after dialysis.…”
Section: Conflict Of Interestmentioning
confidence: 99%
See 1 more Smart Citation